Economic uncertainty before and during the COVID-19 pandemic - Dave Altig; Scott Brent Baker; Jose Maria Barrero; Nicholas Bloom; Phil Bunn; Scarlet Chen; Steven J. Davis; Brent Meyer; Emil Mihaylov; Paul Mizen; Nicholas Parker; Thomas Renault; et al. (Federal Reserve Bank of Atlanta, 2020)
We consider several economic uncertainty indicators for the United States and the UK before and during the COVID-19 pandemic: implied stock market volatility, newspaper-based economic policy uncertainty, twitter chatter about economic uncertainty, subjective uncertainty about future business growth, and disagreement among professional forecasters about future gross domestic product growth. Three results emerge. First, all indicators show huge uncertainty jumps in reaction to the pandemic and its economic fallout. Indeed, most indicators reach their highest values on record. Second, peak amplitudes differ greatly-from an 80 percent rise (relative to January 2020) in two-year implied volatility on the S&P 500 to a 20-fold rise in forecaster disagreement about UK growth. Third, time paths also differ: implied volatility rose rapidly from late February and peaked in mid-March, falling back by late March as stock prices began to recover. In contrast, broader measures of uncertainty peaked later and then plateaued, as job losses mounted, highlighting the difference in uncertainty measures between Wall Street and Main Street.
Keywords: D80; E22; E66; G18; L50; 330; forward-looking uncertainty measures; volatility; COVID-19; coronavirus